Processo de trabalho do supervisor clínico-institucional nos Centros de Atenção Psicossocial (CAPS) na percepção dos supervisores - Silva, Gilson Mafacioli da (2010)
This master‟s thesis had as its aim to describe and analyze the working process of the clinical-institutional supervisors of Psychosocial Health Care Centers (CAPS) in Rio Grande do Sul, from the perception of such workers, who are selected according to the Mental Health Care Coordination of the Health Ministry to perform as supervisors, which is supported by the government directive number 11174/GM of July 7, 2005. The method of such study was an exploratory and descriptive research, with a qualitative approach. Clinical-institutional supervisors of Rio Grande do Sul composed the population under study and were selected from the Clinical- Institutional Supervision of CAPS and Psychosocial Health Care Networks edict of the Health Ministry. Such population was composed by 10 participants, and were sorted out taking into consideration the professional field, enabling data to be proportional and wide in its range. Data collection consisted of semi-structured interviews and non-participant observations. Data collected was analyzed through thematic analysis, enabling the emergence of three thematic axis, that made possible to widen the understanding of such data. Axis 1: dynamics of the working process of the clinical-institutional supervisors, that contained aspects related to such process, including perceptions about the work, such as the task of the supervisor concerning the staff, and the devices/instruments that enabled his actions. Among them, the construction of spaces of listening and talking; the problematization of daily questions of the staff; the collective construction of clinical cases; reading of texts and the professional experience based on the transference at work were highlighted. Axis 2 contained facilitating factors and obstacles regarding the process of clinicalinstitutional supervision. Among facilitating factors, the working experience in collective health was highlighted, and among the obstacles, the precarization of the relationships at work was cited. Axis 3 approached challenges, perspectives and suggestions for the clinical-institutional supervision and the greatest challenges were perceived as related to the implantation and effectiveness of Public Policies. Concerning the perspectives, widening of such proposal to other institutions of the network was evidenced and as regards suggestions, the extension of the supervision period was pointed out. Thus, such study enabled to list some recommendations, and not prescriptions, to the accomplishment of this task.